Pelatihan Aplikasi Adobatola (Administrasi Kependudukan Online Barito Kuala) Disdukcapil Marabahan - Wathani, Muhammad Rais; Kurniawan, Mirza Yogy; Rosadi, Muhammad Edya; Raharjo, Mokhamad Ramdhani; Hasbi, Muhammad; Noor Asegaff, Aulia Rizky M. Hendrik (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
The Civil Registry Service Office of Marabahan began to shift to the use of information technology to improve work efficiency due to access difficulties and time constraints experienced by the community in processing population documents that require physical presence at the service office. So, the Adobatola application was developed, which allows residents to process various population documents online based on mobile. This dedication activity aims to optimize the implementation of the Adobatola application. To achieve this goal, methods such as tutorials, independent practice, and discussions were employed as part of the socialization and training process for using the application. The results of this activity indicate that most of the training participants have acquired the ability and readiness to transition to the application, outnumbering those who are not yet prepared for the migration. The success of this activity is an essential indicator of the implementation of the Adobatola system at Disdukcapil Marabahan, promising efficiency and ease in the management of population documents. In conclusion, integrating information technology through the Adobatola application has successfully improved the population administration process in Marabahan while also opening opportunities for enhancing the quality of public services.